Freely available OPV—The fast way to progress. Issue 7 (2nd July 2013) - Krebs, Frederik C.; Hösel, Markus; Corazza, Michael; Roth, Bérenger; Madsen, Morten V.; Gevorgyan, Suren A.; Søndergaard, Roar R.; Karg, Dieter; Jørgensen, Mikkel
<x xml:space="preserve">Abstract</x> It's a free‐for‐all! ITO‐free organic photovoltaics are fabricated using roll‐to‐roll processing technology and laser cutting to separate and encapsulate individual modules. The modules are then made available free‐of‐charge from the author′s website (in an effort named "freeOPV") to create a platform from which the processing technology can be evaluated using information shared by researchers all over the world.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>